Synthesis of 1 2 4 triazol 4 yl 4 methyl 4 phenyl 3 phenylamino methylazetidin 2 one and their Biological Activities - Lal, Harcharan (International Journal of Pharmaceutical & Biological Archive, 2012)
Synthesis of 1 2 4 triazol 4 yl 4 methyl 4 phenyl 3 phenylamino methylazetidin 2 one and their Biological Activities